2020
DOI: 10.1021/acs.jpcc.0c02628
|View full text |Cite
|
Sign up to set email alerts
|

Interface Modification for Enhanced Efficiency and Stability Perovskite Solar Cells

Abstract: As a superstars of photovoltaic devices, organic–inorganic hybrid perovskite solar cells (PSCs) have garnered plenty of interest due to their superior character. However, many defects, such as carrier recombination, inferior stability, poor interface contact, have prevented their further development. Here, we demonstrate a novel approach of interface engineering to form a compact perovskite layer with decreased defects on SnO2 film by adding tris­(pentafluorophenyl)­boron (TPFPB) as an interfacial modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…[ 62 ] Contrasting with that of the 9CN‐PMI‐modified and control device, the device with 4OH‐NMI showed higher R rec , implying a substantially suppressed charge recombination in the perovskite layer resulting from the reduced surface‐defect states. [ 32,63 ] Finally, the transient photovoltage decay shows that both 4OH‐NMI‐ and 9CN‐PMI‐modified PSCs possess a prolonged decay of 28 and 24 μs compared with the 19 μs of the control device (Figure S8, Supporting Information). The slower photovoltage decay also implied less recombination owing to the efficient trap passivation in the film.…”
Section: Resultsmentioning
confidence: 99%
“…[ 62 ] Contrasting with that of the 9CN‐PMI‐modified and control device, the device with 4OH‐NMI showed higher R rec , implying a substantially suppressed charge recombination in the perovskite layer resulting from the reduced surface‐defect states. [ 32,63 ] Finally, the transient photovoltage decay shows that both 4OH‐NMI‐ and 9CN‐PMI‐modified PSCs possess a prolonged decay of 28 and 24 μs compared with the 19 μs of the control device (Figure S8, Supporting Information). The slower photovoltage decay also implied less recombination owing to the efficient trap passivation in the film.…”
Section: Resultsmentioning
confidence: 99%
“…19,21,[28][29][30][31][32] Therefore, optimizing the electronic properties of the ETL/perovskite interface is one route for achieving hysteresis-free planar PSCs with highest PCEs. Many approaches have been proposed in this regard: (i) a bilayer ETL structure composed of two metal oxide films; [31][32][33][34][35] (ii) doping of the ETL; 5,18,19,36-40 (iii) an interfacial modification at the ETL/ perovskite interface; 30,32,[41][42][43][44][45][46][47][48][49][50][51][52] or (iv) doping the perovskite bulk. [53][54][55][56] Lithium (Li) has been introduced as promising dopant 5,36,[57][58][59][60][61] for improving the ETL/perovskite interface among others.…”
Section: Introductionmentioning
confidence: 99%
“…[280] Li et al reported the interfacial modification using tris(pentafluorophenyl)boron (TPFPB). [281] Subsequently, Tang et al designed hybrid ETL with SnO 2 and carbon nanotubes (CNTs), which effectively improved the conductivity of ETL and reduced the trap state density of SnO 2 films. To prepare the hybrid layer, they used a simple solution method to thermally decompose a mixed solution of SnCl 4 .5H 2 O and the pretreated CNTs.…”
Section: The Role Of Etl In the Performance Of Planar N-i-p Structure...mentioning
confidence: 99%